Diseño organizacional y gestión del talento humano en la distribuidora Ferrocentro Unimax de la ciudad de Loja. - Orozco Serrano, Miguel Arturo (2012)
Planning and talent management is an important tool at the present time to raise awareness and identify situational states that there is an organization against its internal and external environment. For the development of this project was the collection of information by conducting surveys at 17 workers and an interview with the manager in order to obtain information to conduct a situational analysis of Ferrocentro Unimax distributor of the City of Loja, and and know the different problems on Organizational Design and Human Resource Management in the distribution under study, just as the charts were designed structural, functional and positional allowing them to know the hierarchical levels, functions, salaries and name the person occupying the position. It was further stated administrative manuals as functional for identifying the same hierarchical level, code, nature of work, functions, features of the class and personal requirements, it is noted that this objective is not stated by the hand of welcome because that is at the stage of entry of personnel with respect to induction. Likewise design stages of the process of entry of personnel, because the distributor does not apply this process, the two media should be made both internally and externally in order to exist while promotion between outsiders but to provide development and business growth in the research work is recorded as external recruitment should be applied which was proposed by the advertisements in the daily media time, and 99.3 FM radio society. The selection suggests the following process: job application, resume, application form, interview, skills testing, psychological testing, certification of criminal record and medical certificate. In the procurement was conducted through a contract trial work, it has a period of 90 days, and the fixed contract is one year. Within the induction manual was prepared to welcome it will raise awareness to people who are new to work within the organization and includes: welcome letter, the distribution history, mission, vision, objectives and values of the company, hours and days of payment, items offered, personnel policies, location of it, and finally an internal labor regulations. Then we conducted a training plan so that employees acquire knowledge and skills to enable them to perform in a better way, personally and professionally. In regard to the valuation of positions according to the method of assessment was found that 9 points are being unfairly charged and instead paid the 4 are being paid higher than normal, so please keep it fair payment to all staff within the parameters of education, experience, initiative, responsibility and risks of each job. It also should be the policy of the Utility Ferrocentro Unimax Loja City the evaluation of performance enabling them to measure the individual and collective performance of personnel who work in it, which was performed through the graphical scale method Scoring the same which affords an objective assessment of staff development activities that plays in an organization and are given numerical values to each point, in order to obtain various computations also allow us to know how is the staff working Distributed in the factors: timeliness, responsibility, knowledge, leadership and fellowship of each member. Thus, the performance evaluation allowed to know the strengths and weaknesses of staff Ferrocentro Unimax distributor, so as to maintain the strengths also build skills and characteristics and developed through seminars and eliminate the weaknesses, within these has been unable to detect the presence of certain distractions, lack of thought, creativity and initiative of some being the most significant. Subsequently, the findings raised where permitted to know the reality of how the distributor is in regard to organizational development and Human Resource Management. The recommendations made them in order to suggest to the owner or manager to make decisions more appropriate and implement development and growth of the same. The literature was entered in alphabetical order starting from the surname, name, title of work, name of the editing and publication year. The annexes are documents supporting the development of this research work, the same consisting of both the interview format addressed to the Manager of the Utility, as the survey applied to the employees of the same, and photographs of the Distribuidora facilities. Finally the index, which consists of the contents and the number of pages contained in this research work